Laudato Si’ as Soft Law? A Critical Assessment from the Perspective of International Law - Supriyanto, Agustinus (Journal of Ecohumanism, 2026)
This article critically examines whether Pope Francis’ 2015 encyclical Laudato Si’: On Care for Our Common Home can be understood as a form of soft law within international human rights and environmental governance. Employing doctrinal legal analysis combined with conceptual and normative assessment, the study applies established soft law criteria—intent, form, institutional context, subsequent practice, and normative influence—to evaluate the encyclical’s legal significance. The analysis reveals that while Laudato Si’ exhibits significant soft law characteristics and has demonstrably influenced environmental human rights discourse, policy, and advocacy, its foundations in religious authority and lack of formal intergovernmental adoption position it as a hybrid category of "moral soft law" or "transnational normative persuasion." The article concludes by exploring the implications of this finding for the evolving architecture of global environmental governance, arguing that the encyclical’s significance lies in challenging traditional state-centric conceptions of norm-creation while highlighting both the potential and limitations of religious-moral texts in international law.